Biomechanical Effects of Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD), the Major Constituents of Cannabis, in a Sprague Dawley Rat Achilles Tendon Surgical Repair Model: A Pilot Study. Issue 9 (July 2021) - Stauch, Christopher M.; Ammerman, Brittany; Sepulveda, Diana; Aynardi, Michael C.; Garner, Matthew R.; Lewis, Gregory; Morgan, Daniel; Dhawan, Aman
Background: The use of cannabis is common among athletes and the US population at large. Cannabinoids are currently being evaluated as alternatives to opioid medications for chronic pain management. However, the effects of recreational and/or medical use of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) on musculoskeletal injury and healing remain largely unknown. Hypothesis/Purpose: The purpose of this study was to evaluate the biomechanical effects of CBD and THC on tendon-to-tendon healing in a rat Achilles tendon repair model. The hypothesis was that rats administered CBD would demonstrate decreased tensile load to failure of surgically repaired Achilles tendons compared with the THC and control groups. Study Design: Controlled laboratory study. Methods: A total of 33 Sprague Dawley rats underwent Achilles tendon surgical transection and repair and were randomized to receive subcutaneous injection of THC, CBD, or vehicle once daily starting on the day of surgery and for 5 total days. After sacrifice, biomechanical tensile load-displacement testing was performed to determine Achilles tendon load to failure and stiffness. Data were analyzed by 1-way analysis of variance. Results: The THC group demonstrated the highest median load to failure, 18.7 N (95% CI, 15.3-19.2 N); the CBD group had the second highest at 16.9 N (95% CI, 15.1-19.8 N), and the control group had the lowest at 14.4 N (95% CI, 12.1-18.3 N). Stiffness was highest in the THC group at 4.1 N/mm (95% CI, 2.7-5.1 N/mm) compared with 3.6 N/mm (95% CI, 2.9-4.1 N/mm) for the CBD group and 3.6 N/mm (95% CI, 2.8-4.3 N/mm) for the control group. No statistically significant differences for strength and stiffness were observed between the groups. Conclusion: In this pilot study using an animal tendon-to-tendon repair model, neither THC nor CBD resulted in altered biomechanical characteristics compared to control. Clinical Relevance: Cannabinoids do not appear to adversely affect Achilles tendon healing.